TRADITIONAL BELIEFS SEBLANG THE BEHAVIOR OF THE OSING SOCIETY OF BANYUWANGI DISTRICT EAST JAVA PROVINCE - Agus Mursidi; Harwanti Noviandari (Al-Qalam, 2021)
Banyuwangi has various cultural and traditional activities as well as art. One of them is the seblang tradition which is only practiced by the Osing community in Banyuwangi, that is, Bakungan Village and Olehsari Village in Glagah District, Banyuwangi Regency. This research was a qualitative research with a phenomenological approach with 15 informants consisting of community leaders, government, members of community. The results of this study indicated that belief in implementing customs generated the behavior from the results of self-perception which are supported by social perceptions aimed at cleaning the village and rejecting reinforcements. The community's belief in the Seblang tradition is still ingrained and carried out well so that it forms community behavior if it is not carried out, disaster will take place. In the self-perception of the Bakungan and Olesari community, the assumption is that the community members do not celebrate it, they will be ostracized by other communities. However, in its development, the role of government is in hegemony of the community so that custom continue to develop into one of the contestation of customs and tourism.